Pemberdayaan Masyarakat Melalui Produksi Batik Pring Sedapur Di KUBE (Kelompok Usaha Bersama) Mukti Rahayu Kabupaten Magetan - Anisa Auliyaazahra; Sungkowo Edy Mulyono (LPPM Politeknik Pratama, 2024)
The level of poverty in Indonesia is quite high and extreme, one of which is located in East Java Province, especially Magetan Regency, East Java. It is hoped that through this community empowerment program it can increase income. This study aims to describe the implementation of community empowerment through batik Pring Sedapur in KUBE Mukti Rahayu, the achievement of the results obtained, as well as the supporting and inhibiting factors of the empowerment process. This research uses descriptive qualitative research methods. Data collection techniques through observation, interviews, and documentation. For data analysis methods using data reduction, data presentation, and conclusions. The results obtained from the community empowerment process through batik Pring Sedapur go through several stages, namely the awareness stage, the transformation stage, and the intellectual capacity building stage. The achievement of the results obtained from empowerment is through the economic, social, and cultural fields that have been well established. Supporting factors for empowerment include beneficiaries playing an active role, flexible time, and support from the local government. Meanwhile, the inhibiting factor in empowerment is that elderly beneficiaries are difficult to develop and only think about their personal interests.